2019
DOI: 10.1109/access.2019.2920237
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Local and Global Evolution Pattern of Community Structures for Dynamic Networks Analysis

Abstract: Exploring and understanding the temporal structure of dynamic networks attract extensive attention over the past few years. Most of these current research focuses on temporal community detection, evolution analysis or link prediction from a mission-oriented perspective. In fact, these three tasks should be not isolated but mutually reinforcing. Transforming these three tasks into a unified framework, it is crucial to extract the evolution pattern, which helps to understand the time-varying characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…What's more, in [16], CPS is a kind of system supplying the integration of physical processes, computation and networks. It can also be viewed as a system with physical subsystems and software bounded together and each of Multi-scale computation, physical components [12] Information system, sensors, mechanical equipments [13] System, dynamic continuous processes, discrete state transition , heterogeneous composition [14] A system transcends software and control domains, software components [15] Physical subsystems, software,time and space interactions [16] Community detection, evolution analysis, link structure prediction [17] Gathering data, pre-processing data, running analyses, post-processing results [18] them interacts with each other in various time and space dimensions [17,18]. So it is apparent to reach the conclusion that it is system composition that distinguishes CPS from diverse data processing paradigms.…”
Section: Cyber-physical Systemsmentioning
confidence: 99%
“…What's more, in [16], CPS is a kind of system supplying the integration of physical processes, computation and networks. It can also be viewed as a system with physical subsystems and software bounded together and each of Multi-scale computation, physical components [12] Information system, sensors, mechanical equipments [13] System, dynamic continuous processes, discrete state transition , heterogeneous composition [14] A system transcends software and control domains, software components [15] Physical subsystems, software,time and space interactions [16] Community detection, evolution analysis, link structure prediction [17] Gathering data, pre-processing data, running analyses, post-processing results [18] them interacts with each other in various time and space dimensions [17,18]. So it is apparent to reach the conclusion that it is system composition that distinguishes CPS from diverse data processing paradigms.…”
Section: Cyber-physical Systemsmentioning
confidence: 99%
“…Nowadays, with the application of many technologies such as survival analysis techniques [12], matrix factorization [13], and mean-field approximation [14] to solve dynamic network analysis problems, the study of dynamic network evolution models has attracted more and more attention from scholars. Hence, a series of models related to the evolution of public opinion have been studied from various angles [15]- [25], and the evolution of public opinion has received extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks are often dynamically changing during the evolution of public opinion. W Yu found that the results of community detection are not isolated from time changes [13]. Deng J et al also analyzed the dynamic changes of social networks [26].…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of technology demand, edge computing also plays a huge role. Edge computing is an open framework, in which data source close to the edge of the network and integrates core functions, such as grid, storage, computing, application, and provides the nearest edge intelligent service according to the main needs of the current digital industry in data optimization, fast connection, privacy security protection, and so forth [1,2]. However, it cannot be ignored that there are still considerable opportunities and challenges in wireless communication security of edge-cloud computing [3].…”
Section: Introductionmentioning
confidence: 99%